1998
DOI: 10.1002/(sici)1097-4628(19981031)70:5<935::aid-app14>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of readily processable thermoplastic-toughened thermosets. II. Epoxy toughened using a reactive solvent approach

Abstract: ABSTRACT:The fracture toughness of epoxy thermosets was increased by up to 220% using very low-molecular-weight (ϳ 1000 g/mol) imide thermoplastic. The objective was to produce a low-viscosity prepolymer that could be easily autoclave-processed to give a tough thermoset. Here, an homogenous epoxy prepolymer was prepared by first synthesizing very low-molecular-weight linear aromatic imide (ϳ 1000 g/mol) directly in a liquid allyl phenol reactive solvent, followed by dissolution of the epoxy (Epon® 825) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The coatings without and with Vi-PDMS both showed a smooth surface, and the coatings with Vi-PDMS were more opaque [ Figure 6(a,b)]. 23,24 The appearance further confirmed that phase separation occurred in the film-formation process. After ultrasonic treatment, the adhesion of the coatings without Vi-PDMS was affected [ Figure 6(c,d)].…”
Section: Fabrication Of P(ba-mma-vi-pdms)/ca-cpl Latex Via Soap-free mentioning
confidence: 81%
“…The coatings without and with Vi-PDMS both showed a smooth surface, and the coatings with Vi-PDMS were more opaque [ Figure 6(a,b)]. 23,24 The appearance further confirmed that phase separation occurred in the film-formation process. After ultrasonic treatment, the adhesion of the coatings without Vi-PDMS was affected [ Figure 6(c,d)].…”
Section: Fabrication Of P(ba-mma-vi-pdms)/ca-cpl Latex Via Soap-free mentioning
confidence: 81%